Percutaneous Tracheostomy in COVID-19 Critically Ill Patients: Experience from 30 Consecutive Procedures - Bertini, Pietro; Forfori, Francesco; Bruschini, Luca; Corradi, Francesco; Ribechini, Alessandro; Brogi, Etrusca; Guarracino, Fabio (International Archives of Otorhinolaryngology, 2021)
Introduction Percutaneous tracheostomy (PT) in the intensive care unit (ICU) is a well-established practice that shows a reduced risk of wound infection compared with surgical tracheostomy, thus facilitating mechanical ventilation, nursing procedures, reduction in sedation and early mobilization.Objective This is an observational case-control study that compares the results of PT in ICU patients with coronavirus disease 2019 (COVID-19) prospectively enrolled to a similar group of subjects, retrospectively recruited, without COVID-19.Methods Ninety-eight consecutive COVID-19 patients admitted to the ICU at Pisa Azienda Ospedaliero Universitaria Pisana between March 11th and May 20th, 2020 were prospectively studied. Thirty of them underwent PT using different techniques. Another 30 non-COVID-19 ICU patients were used as a control-group. The main outcome was to evaluate the safety and feasibility of PT in COVID-19 patients. We measured the rate of complications.Results Percutaneous tracheostomy was performed with different techniques in 30 of the 98 COVID-19 ICU patients admitted to the ICU. Tracheostomy was performed on day 10 (mean 10 ± 3.3) from the time of intubation. Major tracheal complications occurred in 5 patients during the procedure. In the control group of 30 ICU patients, no differences were found with regards to the timing of the tracheostomy, whereas a statistically significant difference was observed regarding complications with only one tracheal ring rupture reported.Conclusion Percutaneous tracheostomy in COVID-19 patients showed a higher rate of complications compared with controls even though the same precautions and the same expertise were applied. Larger studies are needed to understand whether the coronavirus disease itself carries an increased risk of tracheal damage.
Keywords: ARDS; COVID-19; tracheostomy; percutaneous; surgical